Nonlinear Free Surface Flow past a Wedge in Channel - Tahar BLIZAK; Abdelkader GASMI (université de msila, 2023)
: In this paper, the two-dimensional problem of irrotational flow past a wedge located in the center of the channel is considered. Assuming that the fluid is incompressible and non-viscous, the influence of gravity is ignored but the surface tension is considered. The problem which is characterized by the nonlinear boundary conditions on the free surface of the unknown equation is solved numerically by the series truncation technique. The results show that for all given wedge configurations, there is a critical value for the Weber number, for which there is no solution for every Weber number value smaller than this. In addition, the obtained results extend the work done by Gasmi and Mekias [2]
Keywords: Free surface, Incompressible, Inviscid flow, Capillarity, Surface tension, Series truncation